Novel subcellular localization for α-synuclein: possible functional consequences - Guardia-Laguarta, Cristina; Area-Gomez, Estela; Schon, Eric A.; Przedborski, Serge (Frontiers in Neuroanatomy, 2015)
α−Synuclein (α-syn) is one of the genes that when mutated or overexpressed causes Parkinson’s Disease (PD). Initially, it was described as a synaptic terminal protein and later was found to be localized at mitochondria. Mitochondria-associated membranes (MAM) have emerged as a central endoplasmic reticulum subcellular compartments where key functions of the cell occur. These domains, enriched in cholesterol and anionic phospholipids, are where calcium homeostasis, lipid transfer, and cholesterol metabolism are regulated. Some proteins, related to mitochondrial dynamics and function, are also localized to this area. Several neurodegenerative diseases have shown alterations in MAM functions and resident proteins, including Charcot Marie-Tooth and Alzheimer’s disease. We have recently reported that MAM function is downregulated in cell and mouse models of Parkinson’s disease (PD) expressing pathogenic mutations of α-syn. This review focuses on the possible role of α-syn in these cellular domains and the early pathogenic features of Parkinson’s disease that could be explained by α-syn-MAM disturbances.